(untitled) (International relations and international law Journal, 2025)
The relevance of this study stems from the growing role of Central Asia in global geoeconomic processes. The region lies at the crossroads of key transport routes connecting Europe, Asia, and the Middle East. In recent decades, major world powers – including Russia, China, India, Turkey, the European Union, and the United States - have shown increasing interest in the region’s transport infrastructure. The international projects “North–South” and the “New Silk Road” represent ambitious initiatives aimed at creating alternative transport corridors that could reshape the economic landscape of Central Asia and significantly influence global supply chains. However, their implementation is associated with geopolitical risks, such as intensified competition among major players and the potential for participating countries to fall into debt dependence. The aim of this study is to conduct a comparative analysis of the economic potential and geopolitical risks associated with the “North–South” and “New Silk Road” projects. The research also seeks to assess their impact on development and stability in Central Asia. An important aspect of the study is identifying possible points of convergence and contradiction between the two initiatives, as well as outlining scenarios for their future coexistence. The methodological basis of the research includes comparative analysis, a systems approach, and methods of geoeconomic forecasting. These methods enable a comprehensive examination of the impact of international transport corridors on the region’s economic dynamics and help assess the potential risks linked to their implementation. The practical significance of the study lies in the development of recommendations for policymakers and the business community to minimize geopolitical risks and enhance the economic efficiency of international transport corridors across Eurasia. The results obtained can be used in strategic planning of transport policies in Central Asian countries, as well as in designing measures to optimize logistics and improve the investment appeal of infrastructure projects. The geopolitical aspects of the study include an analysis of the interactions among key players in the region. The “North–South” and “New Silk Road” projects are viewed as instruments of foreign economic influence by Russia, China, and India. The interaction between these countries and their strategic interests in Central Asia can contribute either to enhanced cooperation or the emergence of new geopolitical fault lines. Special attention is given to the influence of transport corridors on regional economic integration and the possible mechanisms for resolving arising contradictions. Thus, this study provides a deeper understanding of the economic and geopolitical processes shaping the development of Central Asia, and offers recommendations for improving the effectiveness of international transport corridors in light of global challenges and regional specificities. Key words: India, Russia, China, New Silk Road, North–South, Central Asia, trade, complementarity, competitive environment.